Implementasi Pendidikan Agama Buddha Berbasis Moralitas Altruis pada SMP Metta Maitreya Pekanbaru - Sonika Sonika (Jurnal Maitreyawira, 2021)
This study focuses on the implementation of altruist moral-based Buddhist education, the sub-focus analysis to implement altruistic moral transformation of SMP Metta Maitreya Pekanbaru. The research design is a qualitative study case which involves principals, Buddhist education teachers, Moral Ethics teachers, and students of SMP Metta Maitreya Pekanbaru. Collecting data by observation, interviews, documentation, and triangulation. Data analysis with interactive model (Miles and Huberman, 1994: 12), through data reduction, data presentation, and conclusions/verification. The validity of the data with the concept of validation is triangulation and member check. The results of the study were revealed : 1) The implementation of Buddhist education in the student test assessment is classified as Good, referring to Minister of National Education Regulation No.19 of 2007 concerning Management of Educational Standard, 2) The implementation of altruistic moral-based learning has not been realized properly and consistently as it’s still a new program which causes school policy apply dynamically. New culture is built from an effective school structure which is forwarded to students to form a school element which is able to protect, love and glorify life to transform the measurable character of appropriate school culture. The school has developed Love Learning in harmony with altruistic morals to enhance positive, non-violent and loving behavior for all school elements in the The School of Universal Family. To shape a new atmospheric academic character which prioritizes the altruist moral values of the Universal Family as the impact/outcome of the SMP Metta Maitreya. KATA KUNCI: Buddhist Education, Moral Altruism, Universal Love.